Pengembangan Sistem Pendukung Keputusan Menggunakan Pendekatan PIPRECIA-S dan ARAS untuk Pemilihan Wireless Repeater - Sah, Andrian; Tanniewa, Adam M. (Bulletin of Data Science, 2024)
A wireless repeater is one of the solutions to extend signal range and reduce dead spot areas. However, selecting the right device often poses challenges for users due to the variety of products available in the market, each with differing specifications, performance, and prices. This study aims to develop a decision support system (DSS) based on the PIPRECIA-S and Additive Ratio Assessment (ARAS) methods. The PIPRECIA-S method is used to determine criterion weights in a structured manner, while the ARAS method evaluates alternatives based on their relative utility. The study resulted in a web-based application designed to enable users to access and manage data anytime and anywhere. A case study demonstrated that TP-Link TL-WA850RE (A4) ranked first with a score of 0.9395, followed by Prolink N300 (A3) with a score of 0.8571, Mercusys MW300RE (A1) with a score of 0.7770, and Tenda A9 (A2) in the last position with a score of 0.7141. The system's calculation results were consistent with manual calculations, proving the system's reliability and validity in providing recommendations. System testing using the black-box testing method showed that all features functioned as specified, including data management, input evaluation, and alternative ranking calculations. This study contributes a systematic solution to assist users in selecting the most suitable wireless repeater for their needs, while also enhancing efficiency in the multi-criteria decision-making process.